2016
DOI: 10.1080/15389588.2016.1153635
|View full text |Cite
|
Sign up to set email alerts
|

Design and cognitive evaluation of 6 dynamic lane departure warning symbols

Abstract: The most considerable result of the current study was the match between the symbol with the highest ratings and the International Organization for Standardization (ISO)-related icon in appearance. Because previous studies demonstrated a strong correlation between comprehension scores of the symbol and both semantic closeness and meaningfulness, high-level comprehensibility of the best ranked symbol is expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Overall, the poster, which was previously validated by a panel of experts and laypeople, had positive results in terms of readability (including understandability) and usefulness among its target population, i.e., caregivers of patients with dysphagia across a range of education levels. Thus, this study adds caregivers of patients with dysphagia to previous research also reporting positive uses of visual signs among staff, including in the context of dysphagia, and among patients in other health areas [16][17][18][19]21,23,24]. Caregivers express the desire for more knowledge about dysphagia procedures and report that communication of this information is often limited or delivered with technical language [7,8,13].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Overall, the poster, which was previously validated by a panel of experts and laypeople, had positive results in terms of readability (including understandability) and usefulness among its target population, i.e., caregivers of patients with dysphagia across a range of education levels. Thus, this study adds caregivers of patients with dysphagia to previous research also reporting positive uses of visual signs among staff, including in the context of dysphagia, and among patients in other health areas [16][17][18][19]21,23,24]. Caregivers express the desire for more knowledge about dysphagia procedures and report that communication of this information is often limited or delivered with technical language [7,8,13].…”
Section: Discussionmentioning
confidence: 90%
“…Designed as an augmentative means of information for caregivers of patients with dysphagia, the poster communicated dysphagia-specific risks and food procedures through visual signs and images accompanied by a few written words. It followed the recommendations for the construction of this type of figurative content and showed effectiveness, including in drawing a caregiver's attention to it, namely, through the use of a warning sign placed at the beginning, which is a well-known sign of danger [18,23,24]. Across a varied range of education levels (from four years of school or less to college degrees), all caregivers who were exposed to the poster (100%) reported that not only did they notice the poster, but they also "read" and understood it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations